Genome-based analysis of the family Paracoccaceae and description of Ostreiculturibacter nitratireducens gen. nov., sp. nov., isolated from an oyster farm on a tidal flat - Huang, Zhaobin; Li, Meiqin; Oren, Aharon; Lai, Qiliang (Frontiers in Microbiology, 2024)
The family Paracoccaceae comprises the majority of the Alphaproteobacteria in marine habitats and displays a large phenotypic, genotypic and metabolic diversity. In this study, two novel strains affiliated to the family Paracoccaceae were isolated from the tidal flat sediments and characterized by a polyphasic taxonomic method. Based on phenotypic, genomic and phylogenetic analysis, the strains represented a novel species within a novel genus, and thus Ostreiculturibacter nitratireducens gen. nov., sp. nov. is proposed. Gene annotation found the strains have a gene cluster for nitrate reduction and a gene cluster for sulfur oxidation, indicating the possible role in N and S cycling in tidal flat sediments. Additionally, phylogenetic analysis found thirty-five species of the family Paracoccaceae needed re-classification, and an AAI value of 70% was chosen as the genus boundary within the family Paracoccaceae. This study further reconstructed the taxonomic framework of the family Paracoccaceae.